1999
DOI: 10.1042/cs0970467
|View full text |Cite
|
Sign up to set email alerts
|

Oximetry spectral analysis in the diagnosis of obstructive sleep apnoea

Abstract: Using spectral analysis of oximetry data, we prospectively evaluated the validity of this methodology in patients clinically suspected of suffering from obstructive sleep apnoea (OSA). A total of 233 outpatients were studied. Nocturnal oximetry was performed simultaneously with conventional polysomnography for all participants. The power density of oxygen saturation was analysed using Fast-Fourier transformation of the oximetric signal. Nocturnal oximetry test results were considered as abnormal (suspicion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 33 publications
3
39
2
6
Order By: Relevance
“…The studies by Rodríguez et al (1996), Lacassagne et al (1997), Zamarrón et al (1999), Olson et al (1999) and Magalang et al (2003) provided higher sensitivity but lower specificity, whereas Ryan et al (1995) and Brouillette et al (2000) achieved higher specificity but lower sensitivity. Our results demonstrate that both CTM and LZ methods provide significant sensitivity and specificity values.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The studies by Rodríguez et al (1996), Lacassagne et al (1997), Zamarrón et al (1999), Olson et al (1999) and Magalang et al (2003) provided higher sensitivity but lower specificity, whereas Ryan et al (1995) and Brouillette et al (2000) achieved higher specificity but lower sensitivity. Our results demonstrate that both CTM and LZ methods provide significant sensitivity and specificity values.…”
Section: Discussionmentioning
confidence: 94%
“…The PSG register was analyzed over periods of 30 s and during sleep phases I, II, III, IV and rapid eye movement, according to R&K rules (Rechtschaffen and Kales 1968). Apnoea was defined as the absence of airflow for more than 10 seconds and hypopnoea as the reduction of respiratory flow for at least 10 seconds accompanied by a 4% or more decrease in the saturation of haemoglobin (Zamarrón et al 1999, Meoli et al 2001. The average apnoea-hypopnoea index (AHI) was calculated for hourly periods of sleep.…”
Section: Subjects and Signalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar features were considered in this study. For the SpO2 signal, previous studies have used temporal features including the percentage time below a certain level, the sum of the differences between successive readings (delta index), the number of dips in oxygen saturation per hour and frequency-based features such as the spectral peak in the SpO2 spectrum and pulse rate periodogram in the range of 30-70 s (Gyulay et al 1993;Golpe et al 1999;Zamarron et al 1999;Oeverland et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Yamashiro & Kryger (1995) used nocturnal oximetry as a screener for OSA and achieved a sensitivity of 90 per cent and specificity of 75 per cent; however, they had to reject 10 per cent of subjects from the study due to poor SpO2 signal quality. In an adult population, Zamarron et al (1999) used spectral analysis of the oximetry signal to screen for OSA and found a sensitivity of 78 per cent and a specificity of 89 per cent.…”
Section: (B ) Apnoea and Hypopnoea Index Estimationmentioning
confidence: 99%